Modelling of auctioning mechanism for solar photovoltaic capacity. Issue 9 (20th October 2016) - Poullikkas, Andreas
Abstract : In this work, a modified optimisation model for the integration of renewable energy sources for power-generation (RES-E) technologies in power-generation systems on a unit commitment basis is developed. The purpose of the modified optimisation procedure is to account for RES-E capacity auctions for different solar photovoltaic (PV) capacity electricity prices. The optimisation model developed uses a genetic algorithm (GA) technique for the calculation of the required RES-E levy (or green tax) in the electricity bills. Also, the procedure enables the estimation of the level of the adequate (or eligible) feed-in-tariff to be offered to future RES-E systems, which do not participate in the capacity auctioning procedure. In order to demonstrate the applicability of the optimisation procedure developed the case of PV capacity auctioning for commercial systems is examined. The results indicated that the required green tax, in order to promote the use of RES-E technologies, which is charged to the electricity customers through their electricity bills, is reduced with the reduction in the final auctioning price. This has a significant effect related to the reduction of electricity bills.